2017
DOI: 10.1021/acs.jpca.6b12253
|View full text |Cite
|
Sign up to set email alerts
|

“Watching” the Dark State in Ultrafast Nonadiabatic Photoisomerization Process of a Light-Driven Molecular Rotary Motor

Abstract: Photoisomerization dynamics of a light-driven molecular rotary motor, 9-(2-methyl-2,3-dihydro-1H-cyclopenta[a]naphthalen-1-ylidene)-9H-fluorene, is investigated with trajectory surface-hopping dynamics at the semiempirical OM2/MRCI level. The rapid population decay of the S excited state for the M isomer is observed, with two different decay time scales (500 fs and 1.0 ps). By weighting the contributions of fast and slow decay trajectories, the averaged lifetime of the S excited state is about 710 fs. The calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 65 publications
8
65
0
Order By: Relevance
“…However, the calculations are not entirely self‐consistent. Two suggest that dynamics involve a crossing of two excited states, while two others find that the dynamics occur on a single PES ,. Furthermore, two have investigated the entire 1 a / 1 b PES in both ground and excited states, which has not yet been characterized experimentally.…”
Section: Figuresupporting
confidence: 85%
See 3 more Smart Citations
“…However, the calculations are not entirely self‐consistent. Two suggest that dynamics involve a crossing of two excited states, while two others find that the dynamics occur on a single PES ,. Furthermore, two have investigated the entire 1 a / 1 b PES in both ground and excited states, which has not yet been characterized experimentally.…”
Section: Figuresupporting
confidence: 85%
“…Pang et al. found that the S 1 surface had a single minimum, independent of the initial geometry . If that were the case then the observed difference in lifetime for that common state must reflect dynamical effects, that is, the pathway from the different initial geometries, rather than the final state reached.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, many studies have been carried out with the aim of understanding the details of the potential energy surface (PES) structures and non-adiabatic coupling (NAC) profiles to determine the rotational degrees of freedom and to simulate fast photoisomerization processes in molecular motors systems [12][13][14][15][16][17][18][19]. In contrast, the thermalization process, * ikeda.tatsushi.37u@kyoto-u.jp † A.G.Dijkstra@leeds.ac.uk ‡ tanimura.yoshitaka.5w@kyoto-u.jp which is known as a rate-limiting step of molecular motors [6][7][8], has not been well explored.…”
Section: Introductionmentioning
confidence: 99%